PENGEMBANGAN BAHAN AJAR HYPERMEDIA BERBASIS KELORA DENGAN MODEL QUANTUM TEACHING SISWA KELAS IV SD DI KECAMATAN PECANGAAN KABUPATEN JEPARA - Nurul Hidayah (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this research is to analyze the needs of teaching materials, to design teaching materials, to analyze the effectiveness of the needs of teaching materials. The research method uses R&D. The resulting product is in the form of kelora-based hypermedia teaching materials with a quantum teaching model. The research and development steps refer to Borg and Gall. Data obtained from interviews, questionnaires, and tests. Data were analyzed by accumulating the number of scores. The effectiveness of learning material data was analyzed by normality test, homogeneity test, gain test, t test at a significance level of 0.05 using SPSS. The results of research and development are hypermedia teaching materials based on Jepara local wisdom with a quantum teaching model. This product proved to be feasible because the total scores obtained by the validators of teaching materials, materials and practices were 90.63; 90.27, and 90.25 “very feasible” criteria. The results of the responses from students were 88.89% and the responses of teachers in three elementary schools with an average of 88.24% with the product category "very feasible". The use of this product is effective in improving student learning outcomes. The average percentage of the pretest in the control and experimental classes was almost the same, namely 67.29 and 64.71. After being given treatment, the average posttest of the control and experimental classes increased to 75.53 and 89.41. The results of the t test obtained t value = 6.045 with a significance level of 0.000 < = 0.05.